The discrete mathematics of computing in remote teaching - Avila, Heitor Silva; Foss, Luciana; Cavalheiro, Simone André da Costa (Seven Editora, 2023)
During Emergency Remote Teaching, several obstacles were encountered in teaching logical and mathematical foundations and teaching discrete mathematics to those entering Computing courses. The distance directly impacted the way in which content was approached: concepts were presented in asynchronous video classes and doubts were resolved in synchronous meetings. However, even with the possibility of a replay, there were still students who were unable to fully understand the concepts in a satisfactory manner. Due to factors like this, the remote monitoring project was designed for the Discrete Systems discipline in the Computer Science and Computer Engineering courses at the Federal University of Pelotas. DOI:https://doi.org/10.56238/sevened2023.006-065